2008
DOI: 10.1242/jcs.022210
|View full text |Cite
|
Sign up to set email alerts
|

AQP2 exocytosis in the renal collecting duct – involvement of SNARE isoforms and the regulatory role of Munc18b

Abstract: Vasopressin regulates the fusion of the water channel aquaporin 2 (AQP2) to the apical membrane of the renal collecting-duct principal cells and several lines of evidence indicate that SNARE proteins mediate this process. In this work MCD4 renal cells were used to investigate the functional role of a set of Q- and R-SNAREs, together with that of Munc18b as a negative regulator of the formation of the SNARE complex. Both VAMP2 and VAMP3 were associated with immunoisolated AQP2 vesicles, whereas syntaxin 3 (Stx3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 74 publications
2
45
0
Order By: Relevance
“…Our observation that SYP121-Sp2 fragments from Arabidopsis and maize decreased the plasma membrane trafficking of mYFP:ZmPIP2;5 in tobacco epidermal cells and maize mesophyll protoplasts demonstrates that the mechanism of SYP121-mediated plasma membrane anchoring of PIP2 aquaporins is conserved between monocots and dicots. In addition, the localization of the human AQP2 at the apical membrane of epithelial cells of the collecting duct is also specifically regulated by the syntaxin-3, SNARE-associated protein Snapin and SNAP33 complex (Procino et al, 2008;Mistry et al, 2009), suggesting that the relative abundance of plasma membrane aquaporins is regulated by SNARE complexes in all eukaryotes.…”
Section: Discussionmentioning
confidence: 99%
“…Our observation that SYP121-Sp2 fragments from Arabidopsis and maize decreased the plasma membrane trafficking of mYFP:ZmPIP2;5 in tobacco epidermal cells and maize mesophyll protoplasts demonstrates that the mechanism of SYP121-mediated plasma membrane anchoring of PIP2 aquaporins is conserved between monocots and dicots. In addition, the localization of the human AQP2 at the apical membrane of epithelial cells of the collecting duct is also specifically regulated by the syntaxin-3, SNARE-associated protein Snapin and SNAP33 complex (Procino et al, 2008;Mistry et al, 2009), suggesting that the relative abundance of plasma membrane aquaporins is regulated by SNARE complexes in all eukaryotes.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Critical protein/protein interactions that orchestrate the regulated and constitutive trafficking of AQP2 have been extensively investigated and include actin and microtubules, SNAREs, Rab proteins, heat shock protein 70, clathrin, and others. [6][7][8][9] However, emerging data from AQP2 knockout and transgenic animals suggested an unusual aspect of AQP2 biology. As expected, induction of AQP2 deficiency in mice results in a urinary concentrating defect known as diabetes insipidus (DI).…”
mentioning
confidence: 99%
“…A mouse collecting duct cell line stably transfected with human AQP2, MDC4 cells, was used to further investigate the effect of fluvastatin on AQP2 exosome excretion. We previously showed that in this cell line incubation with fluvastatin nicely accumulates AQP2 at the apical plasma membrane [27,31]. Cells were either left untreated (Ctr) or treated with forskolin 100 µM (FK) or fluvastatin 5 µM (Flu) for 16 hours in the culture medium, then subjected to immunofluorescence protocol to visualize AQP2 cellular distribution.…”
Section: In Vitro Study-fluvastatin Effect On Aqp2 Release In the Culmentioning
confidence: 99%